El papel de la región de la ASEAN en la futura economía global - Daquila, Teófilo C. (1997)
Provides a retrospective assessment of ASEAN’s role in the last 30 years, and analysis of current issues and some trends or prospects for its future in relation to the global economy. He points out that this region has positioned itself as the third most important region in exports, imports and investments, while, in the political aspect, due to its strategic location, it provides security and stability to the world and the Asia Pacific region. He analyzes the factors that impact the role of ASEAN: regional trade agreements in the world, its relations with Europe, the APEC forum and the WTO. He also describes his measures to liberalize this commercialization of goods, services and investment, his response to the financial crisis and to political security problems. It is concluded that the global economy is heading towards freedom of trade and investment, while ASEAN will continue to grow dynamically and become an important factor in the economic and political role.